Fruit carbohydrate metabolism in an introgression line of tomato with increased fruit soluble solids. - Baxter, C; Carrari, F; Bauke, A; Overy, S; Hill, SA; Quick, P; Fernie, A; Sweetlove, L (2005)
A tomato line (IL9-2-5) of the cultivated species, Lycopersicon esculentum, carrying a 9 cM introgression from the wild species, Lycopersicon pennelli, produces fruit with high soluble solids content (Brix), an important determinant of fruit quality for processing. Two quantitative trait loci (QTLs) relating to fruit soluble solids content have been identified within the introgressed segment. One of these QTLs (PW-9-2-5) is silent under the growth conditions used in this study, while a second (Brix-9-2-5) has been shown to encode a fruit apoplastic invertase (Lin5) with altered kinetic properties. In this study, we have undertaken a detailed biochemical analysis of the introgression line to attempt to gain an understanding of the metabolic changes associated with increased fruit soluble solids. Increased Brix in ripe fruit was shown to be the result of increased sucrose and glucose, with a more minor contribution from aspartate and alanine. The introgression leads to a pronounced increase in apoplastic invertase activity in the columella tissue that extends throughout fruit development. Furthermore, columella tissue from IL9-2-5 fruit has a greater capacity to take up exogenously supplied sucrose, an observation that is consistent with the kinetic properties of the introgressed Lin5 allele. Apart from the increase in mature fruit sugar and increases in some amino acids, metabolite profiling revealed few other metabolic perturbations in fruit from IL9-2-5. The only other major change was a dramatic increase in starch accumulation at earlier stages of fruit metabolism. This occurred without any increase in the activity of the enzymes of sucrose metabolism or starch synthesis and may therefore be driven by increased availability of sucrose. We conclude that the major factor that leads to increased fruit sugar in IL9-2-5 is an increase in the capacity to take up sucrose unloaded from the phloem.